2018
DOI: 10.1021/acs.macromol.7b02566
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metal Carboxylate as an Efficient and Simple Catalyst for Ring-Opening Polymerization of Cyclic Esters

Abstract: Alkali metal carboxylates were discovered as efficient and simple catalysts for the ring-opening polymerization of cyclic esters that are alternatives to conventional metal-based catalysts and organocatalysts. In our system using an alcohol initiator and this simple catalyst, biodegradable and biocompatible aliphatic polyesters, such as poly(lactide), poly(ε-caprolactone), poly(δ-valerolactone), and poly(trimethylene carbonate), were obtained with predictive molecular weights ranging from 3500 to 22 600 and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 35 publications
4
66
0
Order By: Relevance
“…The fast insertion of CO 2 into the Co-O bond prevented various side reactions, such as alkoxy chain end formation and subsequent intramolecular and/or intermolecular transesterification, as well as epoxide homopolymerization. Quantitative 13 C NMR analysis suggested that the terpolymers had junction unit contents of up to 40%. To the best of our knowledge, this is the only example of a statistical carbonate/ester terpolymer in which the two components are distributed in the polymeric backbone based on probability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fast insertion of CO 2 into the Co-O bond prevented various side reactions, such as alkoxy chain end formation and subsequent intramolecular and/or intermolecular transesterification, as well as epoxide homopolymerization. Quantitative 13 C NMR analysis suggested that the terpolymers had junction unit contents of up to 40%. To the best of our knowledge, this is the only example of a statistical carbonate/ester terpolymer in which the two components are distributed in the polymeric backbone based on probability.…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative to fermentative synthesis, PHB can also be produced by the catalytic ring-opening polymerization of β-butyrolactone, a low-cost and readily available feedstock generated from the carbonylation of epoxides [7][8][9][10] . Commonly, the nucleophilic ring opening of lactones occurs at the ester group through the cleavage of an acyl C(=O)-O bond, leading to the formation of alkoxy chain ends [11][12][13][14] . However, alkoxy chain ends can react with not only the ester groups of lactone monomers but also the ester groups of the resulting polyester backbone via intramolecular and/or intermolecular (a)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGA was used to evaluate the thermal stability of Fe 3 O 4 @PZS@HMP 1 catalysts. The initial decomposition starts at approximately 150 C, indicating that the catalysts remain thermal stable during the ROP process of δ-VL or ε-CL where the reaction is usually conducted at the temperature of 80-100 C. 58,59 The weight loss was reduced from 96.64% to 76.21% at the temperature range from 150 to 330 C, which is attributed to the decomposition of HMP 1 , and the decomposition of PZS occurred at 410 500 C (ESI †, Figure S2d).…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, biodegradable polymers have been studied in detail and some are currently utilized in industrial processes and consumer goods. Biodegradable polymers can be categorized as those made from modified natural materials, biosynthesized using microorganisms, and chemically synthesized in conjunction with catalysis . The last category has attracted particular attention as it is associated with simple molecular designs, facile synthetic processes and inexpensive raw materials.…”
Section: Introductionmentioning
confidence: 99%